Manipulation of focal Wnt activity via synthetic cells in a double‐humanized zebrafish model of tumorigenesis. Issue 11 (5th January 2021) - Wang, Lei; Long, Jiang; Chen, Huan; Sun, Shaoyang; Lv, Kunpeng; Li, Qiang; Wang, Xu
Abstract: The canonical Wnt signaling pathway is activated in numerous contexts, including normal and cancerous tissues. Here, we describe a synthetic cell‐based therapeutic strategy that inhibits aberrant Wnt activity in specific focuses without interfering with the normal tissues in vivo. As a proof of principle, we generated a triple transgenic zebrafish liver cancer model that conditionally expressed human MET and induced ectopic Wnt signaling in hepatocytes. Then, we generated a customized synthetic Notch receptor (synNotch) cascade to express Wnt inhibitor DKK1 in Jurkat T cells and human peripheral blood mononuclear cells (PBMCs) after recognizing MET as antigen. After that, the synNotch PBMCs were sorted and microinjected into different tissues of the zebrafish model. In MET‐expressing cancerous liver tissues, the injected cells expressed DKK1 and inhibited the local proliferation and Wnt activity; while in the yolk sac without MET, the injected cells remained inactive. Overall, our studies revealed the use of synthetic cells with antigen receptors to improve the spatiotemporal accuracy of anti‐Wnt therapy, and proposed that the genetically humanized zebrafish model may serve as a small‐scale and highly optically accessible platform for the functional evaluation of human synthetic cells. Abstract : What's new? Aberrant regulation of the Wnt signaling pathway plays a critical role in cancer pathogenesis. Despite extensive knowledge of this pathway, however, drugs targeting Wnt and Wnt family proteins have shown limited promise. Here, using synthetic cells and a double‐humanized zebrafish model system, the authors generated MET‐targeting synthetic Notch cells expressing the negative Wnt regulator Dickkopf‐1 (DKK1). Upon injection into the hepatic region of zebrafish, synNotch‐modified peripheral blood mononuclear cells recognized MET antigens, leading to conditional DKK1 expression and Wnt repression. The findings demonstrate the successful application of synthetic cells and a small animal model to the design of Wnt‐targeting therapies.